2016
DOI: 10.3389/fnhum.2016.00251
|View full text |Cite
|
Sign up to set email alerts
|

Holding Biological Motion in Working Memory: An fMRI Study

Abstract: Holding biological motion (BM), the movements of animate entities, in working memory (WM) is important to our daily life activities. However, the neural substrates underlying the WM processing of BM remain largely unknown. Employing the functional magnetic resonance imaging (fMRI) technique, the current study directly investigated this issue. We used point-light BM animations as the tested stimuli, and explored the neural substrates involved in encoding and retaining BM information in WM. Participants were req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 79 publications
1
48
1
Order By: Relevance
“…Additionally, it is important to note that researchers have suggested that there might be two distinct types of social WM (Lieberman, ; Xin & Lei, ): One requires participants to internally focus their attention on friends' internal traits and rank them according to a specific dimension (i.e., internally orientated social WM; e.g., Meyer & Lieberman, , ; Meyer et al., , ); the other requires participants to focus their attention on the external world and their friends' faces or actions (externally orientated social WM; e.g., Gao et al., , ; Lu et al., ; Shen et al., ; Thornton & Conway, ; Xin & Lei, ). Xin and Lei () elegantly showed that there are certain differences in the neural substrates of these two types of social WM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, it is important to note that researchers have suggested that there might be two distinct types of social WM (Lieberman, ; Xin & Lei, ): One requires participants to internally focus their attention on friends' internal traits and rank them according to a specific dimension (i.e., internally orientated social WM; e.g., Meyer & Lieberman, , ; Meyer et al., , ); the other requires participants to focus their attention on the external world and their friends' faces or actions (externally orientated social WM; e.g., Gao et al., , ; Lu et al., ; Shen et al., ; Thornton & Conway, ; Xin & Lei, ). Xin and Lei () elegantly showed that there are certain differences in the neural substrates of these two types of social WM.…”
Section: Discussionmentioning
confidence: 99%
“…If the child could not focus on a trial because of unexpected issues, experimenter presented the same trial again by pressing the space bar on the keyboard. Note that previous studies added a digit rehearsal task to the memory task to prevent participants from verbally encoding BM stimuli (e.g., Gao et al., ; Lu et al., ; Shen et al., ). However, we did not do this because children do not develop verbal rehearsal strategies until around 7 years old (Hitch et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies using multivariate pattern analysis (MVPA) have successfully decoded the specific motion direction during the delay period in MT areas (Emrich, Riggall, LaRocque, & Postle, ; LaRocque, Riggall, Emrich, & Postle, ). Nevertheless, in another study of action VSTM using point‐light motion animations, it has been found that the frontal and parietal lobules were involved in maintaining action during the delay (Lu et al, ). As this study did not include the VSTM task for objects and spatial locations, it remains unclear if these regions are specific to VSTM of actions or they are shared by VSTM of other stimuli (or aspects of stimuli) such as objects/agents or spatial locations.…”
Section: Introductionmentioning
confidence: 99%